How can African agriculture adapt to climate change: The impact of climate variability and climate change on water and food outcomes: A framework for analysis - Ringler, Claudia (Research briefs, 2008)
Over the coming decades, global change will have an impact on food and water security in significant and highly uncertain ways, and there are strong indications that developing countries will bear the brunt of the adverse consequences, particularly from climate change. This is largely because poverty levels are high, and developing-country capacity to adapt to global change is weak. Furthermore, the rural populations of developing countries—for whom agricultural production is the primary source of direct and indirect employment and income—will be most affected due agriculture’s vulnerability to global change processes. The agricultural sector is the largest consumer of water resources, and variability in water supply has a major influence on health and welfare in poor areas. With water scarcity and extreme weather events expected to increase under climate change, water security could decline significantly in rural areas. Consequently, it is important to understand the impacts of global change (in terms of climate, demography, technology, and so on) on agriculture and natural resources in developing countries and to develop adaptive capacity to respond to these impacts. Moreover, there is a need to develop informed and effective adaptation measures and investment options that can be taken now to alleviate adverse impacts of global change in the future.
openalex: W2612149049 mag: 2612149049
Keywords: openalex:import

Mapping South African Farming Sector Vulnerability to Climate Change and Variability: A Subnational Assessment - Gbetibouo, Glwadys Aymone; Ringler, Claudia (RePEc: Research Papers in Economics, 2008)
This paper analyzes the vulnerability of South African farmers to climate change and variability by developing a vulnerability index and comparing vulnerability indicators across the nine provinces of the country. Nineteen environmental and socio-economic indicators are identified to reflect the three components of vulnerability: exposure, sensitivity, and adaptive capacity. The results of the study show that the regions most vulnerable to exposure to extreme events and climate change and variability, do not always overlap with the most vulnerable populations. Furthermore, vulnerability to climate change and variability is intrinsically linked with social and economic development. The Western Cape and Gauteng provinces, with the high level of infrastructure development, high literacy rates, and low share of agricultural GDP, are lower on the vulnerability index; whereas, the most vulnerable regions Limpopo, Kwazulu Natal and Eastern Cape, are those with high number of small-scale farmers, high dependency on rainfed agriculture, high land degradation, and highly populated rural areas where the majority of the population relies on agriculture for their livelihoods. These large differences in the extent of vulnerability between provinces suggest that policy makers should develop region-specific policies and address climate change at the local level.
openalex: W1576292879 mag: 1576292879
Keywords: openalex:import

How can African agriculture adapt to climate change: Mapping the South African farming sector’s vulnerability to climate change and variability: A subnational assessment - Gbetibouo, Glwadys Aymone; Ringler, Claudia (Research briefs, 2009)
In southern Africa, by the middle of the 21st century climate change is expected to cause temperature increases of 1–3°C, broad summer rainfall reductions of 5–10 percent, and an increase in the incidence of both droughts and floods. Consequently, climate change has significant potential to negatively affect crop production in South Africa, and in turn the well-being of the country’s farmers. This brief is based on a study that examines the level of vulnerability to climate change in South Africa’s farming sector by developing a nationwide provincial-level vulnerability profile. Particular attention is paid to the underlying socioeconomic and institutional factors that determine how farmers respond to and cope with climate hazards.
openalex: W3121488329 mag: 3121488329
Keywords: openalex:import

How can African agriculture adapt to climate change: Mapping the South African farming sector’s vulnerability to climate change and variability: A subnational assessment - Gbetibouo, Glwadys Aymone; Ringler, Claudia (RePEc: Research Papers in Economics, 2009)
In southern Africa, by the middle of the 21st century climate change is expected to cause temperature increases of 1–3°C, broad summer rainfall reductions of 5–10 percent, and an increase in the incidence of both droughts and floods. Consequently, climate change has significant potential to negatively affect crop production in South Africa, and in turn the well-being of the country’s farmers. This brief is based on a study that examines the level of vulnerability to climate change in South Africa’s farming sector by developing a nationwide provincial-level vulnerability profile. Particular attention is paid to the underlying socioeconomic and institutional factors that determine how farmers respond to and cope with climate hazards.
openalex: W1551587367 mag: 1551587367
Keywords: openalex:import

Climate change impacts in Ethiopia hydro-economic modeling projections - You, Gene Jiing‐Yun; Ringler, Claudia (2009)
openalex: W11616478 mag: 11616478
Keywords: openalex:import

Measuring Ethiopian farmers’ vulnerability to climate change across regional states - Deressa, Temesgen; Hassan, Rashid M.; Ringler, Claudia (RePEc: Research Papers in Economics, 2008)
This study analyzes the vulnerability of Ethiopian farmers to climate change based on the integrated vulnerability assessment approach using vulnerability indicators. The vulnerability indicators consist of the different socioeconomic and biophysical attributes of Ethiopia's seven agriculture-based regional states. The different socioeconomic and biophysical indicators of each region collected have been classified into three classes, based on the Intergovernmental Panel on Climate Change's (IPCC 2001) definition of vulnerability, which consists of adaptive capacity, sensitivity, and exposure. The results indicate that the relatively least-developed, semiarid, and arid regions—namely, Afar and Somali—are highly vulnerable to climate The Oromia region—a wide region characterized both by areas of good agricultural production in the highlands and midlands and by recurrent droughts, especially in the lowlands—is also vulnerable. The Tigray region, which is characterized by recurrent drought, is also vulnerable to the negative impacts of climate change in comparison with the other regions. Thus, investing in the development of the relatively underdeveloped regions of Somali and Afar, irrigation for regions with high potential, early warning systems to help farmers better cope in times of drought, and production of drought-tolerant varieties of crops and species of livestock can all reduce the vulnerability of Ethiopian farmers to climate change. from authors' abstract
openalex: W1521284118 mag: 1521284118
Keywords: openalex:import

Assessing household vulnerability to climate change: The case of farmers in the Nile basin of Ethiopia. - Deressa, Temesgen; Hassan, Rashid M.; Ringler, Claudia (RePEc: Research Papers in Economics, 2009)
openalex: W1552713248 mag: 1552713248
Keywords: openalex:import

How can African agriculture adapt to climate change: Climate variability and maize yield in South Africa: - Akpalu, Wisdom; Hassan, Rashid M.; Ringler, Claudia (Research briefs, 2008)
Maize is the primary food staple in southern Africa, and 50 percent of the total maize output in the area is produced in South Africa, where maize constitutes approximately 70 percent of grain production and covers 60 percent of the country's cropping area. Climate change could have a significant impact on South African maize production. The scientific community has established that the temperature in South Africa increased significantly between 1960 and 2003 (by 0.13 degrees Celsius), and further temperature increases and changes in the quantity and pattern of rainfall are expected despite any attempts by the international community to reduce greenhouse gas emissions. Although the maize plant is quite hardy and adaptable to harsh conditions, warmer temperatures and lower levels of precipitation could have detrimental effects on yields, thereby increasing food insecurity in the region. This brief is based on a paper that uses household survey data to explore the direct impact of climate variability, measured by changes in temperature and precipitation, on maize yields in the Limpopo Basin of South Africa.
openalex: W2607853572 mag: 2607853572
Keywords: openalex:import

How can African agriculture adapt to climate change: Measuring Ethiopian farmers’ vulnerability to climate change across regional states [in Amharic]: - Deressa, Temesgen; Hassan, Rashid M.; Ringler, Claudia (Research briefs, 2008)
agricultural sector, which is dominated by smallscale, mixed crop, and livestock farming, is the mainstay of the country’s economy. It constitutes more than half the nation’s gross domestic product (GDP), generates more than 85 percent of the foreign exchange earnings, and employs about 80 percent of the population. Ethiopia’s dependence on agriculture makes the country particularly vulnerable to the adverse impacts of climate change on crop and livestock production. This brief is based on a paper that analyzes the vulnerability of Ethiopian farmers to climate change by creating a vulnerability index and comparing vulnerability indicators across regions. A regional vulnerability index can assist in identifying the areas of Ethiopia that are most vulnerable to climate change and guide policymakers in determining where investments in adaptation may be most effective in reducing the future adverse effects of climate change. from text
openalex: W2609664723 mag: 2609664723
Keywords: openalex:import

Measuring Ethiopian farmers' vulnerability to climate change across regional states [in Amharic]: - Deressa, Temesgen; Hassan, Rashid M.; Ringler, Claudia (RePEc: Research Papers in Economics, 2008)
agricultural sector, which is dominated by smallscale, mixed crop, and livestock farming, is the mainstay of the country's economy. It constitutes more than half the nation's gross domestic product (GDP), generates more than 85 percent of the foreign exchange earnings, and employs about 80 percent of the population. Ethiopia's dependence on agriculture makes the country particularly vulnerable to the adverse impacts of climate change on crop and livestock production. This brief is based on a paper that analyzes the vulnerability of Ethiopian farmers to climate change by creating a vulnerability index and comparing vulnerability indicators across regions. A regional vulnerability index can assist in identifying the areas of Ethiopia that are most vulnerable to climate change and guide policymakers in determining where investments in adaptation may be most effective in reducing the future adverse effects of climate change. from text
openalex: W1549783506 mag: 1549783506
Keywords: openalex:import

Measuring Ethiopian farmers' vulnerability to climate change across regional states [in Amharic]: - Deressa, Temesgen; Hassan, Rashid M.; Ringler, Claudia (Research briefs, 2008)
agricultural sector, which is dominated by smallscale, mixed crop, and livestock farming, is the mainstay of the country's economy. It constitutes more than half the nation's gross domestic product (GDP), generates more than 85 percent of the foreign exchange earnings, and employs about 80 percent of the population. Ethiopia's dependence on agriculture makes the country particularly vulnerable to the adverse impacts of climate change on crop and livestock production. This brief is based on a paper that analyzes the vulnerability of Ethiopian farmers to climate change by creating a vulnerability index and comparing vulnerability indicators across regions. A regional vulnerability index can assist in identifying the areas of Ethiopia that are most vulnerable to climate change and guide policymakers in determining where investments in adaptation may be most effective in reducing the future adverse effects of climate change. from text
openalex: W3121488479 mag: 3121488479
Keywords: openalex:import

How can African agriculture adapt to climate change: Are soil and water conservation technologies a buffer against production risk in the face of climate change?: - Kato, Edward; Ringler, Claudia; Yesuf, Mahmud; Bryan, Elizabeth (RePEc: Research Papers in Economics, 2009)
The agricultural sector in developing countries is particularly vulnerable to the adverse impacts of climate change. Given Ethiopia's dependence on agriculture and natural resources, any adverse agricultural effects will pose serious risks to economic growth and livelihoods across the country. Soil and water conservation technologies have been suggested as a key adaptation strategy for developing countries, particularly those in Sub-Saharan Africa, in light of increased water shortages, drought, desertification, and worsening soil conditions. According to a survey of 1,000 households in the Nile Basin of Ethiopia, more than 30 percent of farmers adopted soil and water conservation measures in response to perceived long-term changes in temperature and rainfall. Although soil and water conservation technologies are generally considered low-cost, they still engender risk for very low-income, risk-averse households, which are prevalent in rural Ethiopia. Thus, it is important to consider the impacts not only on crop yields, but also on risk levels. This brief is based on a study that investigates the risk implications of various soil and water conservation technologies for crop production in Ethiopia's Nile River Basin. The analysis identifies technologies that increase and decrease crop production risk-with risk defined as the degree of yield variability-for the purpose of isolating which technologies are best suited to particular regions and agroecological zones. These results could be used to improve the geographical targeting of soil conservation techniques as part of efforts to promote farm-level adaptation to climate change.
openalex: W1562277865 mag: 1562277865
Keywords: openalex:import

How can African agriculture adapt to climate change: Global carbon markets: Are there opportunities for Sub-Saharan Africa? - Bryan, Elizabeth; Akpalu, Wisdom; Ringler, Claudia; Yesuf, Mahmud (Research briefs, 2008)
Human activities such as fossil fuel burning and deforestation have significantly increased the atmospheric concentration of greenhouse gases (GHG) leading to global climate change. Global climate change and its associated weather extremes pose considerable challenges worldwide, and mitigating the adverse impacts of climate change is a high priority for the international community. To reduce global emissions and curb the threat of climate change, many countries are participating in carbon trading. Carbon trading includes allowance-based agreements that impose national caps on emissions and allow participating countries to engage in emission trading as well as project-based transactions (for example, through the CDM or Clean Development Mechanism). The CDM allows industrialized countries with greenhouse gas reduction commitments to invest in emission-reducing projects in developing countries as an alternative to generally more costly emission reductions in their own countries. Funds made available by the CDM for carbon offsets provide an opportunity for cash-strapped developing countries to fund much needed adaptation measures. The potential annual value stream for Sub-Saharan Africa from mitigating GHG emissions is estimated to be US$4.8 billion at carbon prices of US$0–20/tCO2e. Moreover, agricultural mitigation measures, including soil and water conservation and agroforestry practices, also enhance ecosystem functioning, providing resilience against droughts, pests, and climate-related shocks. Yet the potential for Africa to contribute to global reductions in GHG emissions is quite substantial. Estimates suggest Africa could potentially contribute to GHG reductions of 265 MtCO2e (million tons of carbon dioxide or equivalent) per year at carbon prices of up to US$20 through agricultural measures and 1,925 MtCO2e/yr at carbon prices of up to US$100/tCO2e by 2030 through changes in the forestry sector. These amounts constitute 17 and 14 percent, respectively, of the global total potential for mitigation in these sectors. However, countries in Sub-Saharan Africa are marginalized in global carbon markets. Sub-Saharan Africa’s share of the CDM market is nine times smaller than its global share of GHG emissions, including emissions from land use and land-use change. This brief is based on a paper that examines Sub-Saharan Africa’s current involvement in carbon markets, potential for GHG emission reductions, constraints to further participation in carbon markets, and opportunities for expanding Sub-Saharan Africa’s market share.
openalex: W2608095564 mag: 2608095564
Keywords: openalex:import

How can African agriculture adapt to climate change: Are soil and water conservation technologies a buffer against production risk in the face of climate change?: - Kato, Edward; Ringler, Claudia; Yesuf, Mahmud; Bryan, Elizabeth (Research briefs, 2009)
The agricultural sector in developing countries is particularly vulnerable to the adverse impacts of climate change. Given Ethiopia's dependence on agriculture and natural resources, any adverse agricultural effects will pose serious risks to economic growth and livelihoods across the country. Soil and water conservation technologies have been suggested as a key adaptation strategy for developing countries, particularly those in Sub-Saharan Africa, in light of increased water shortages, drought, desertification, and worsening soil conditions. According to a survey of 1,000 households in the Nile Basin of Ethiopia, more than 30 percent of farmers adopted soil and water conservation measures in response to perceived long-term changes in temperature and rainfall. Although soil and water conservation technologies are generally considered low-cost, they still engender risk for very low-income, risk-averse households, which are prevalent in rural Ethiopia. Thus, it is important to consider the impacts not only on crop yields, but also on risk levels. This brief is based on a study that investigates the risk implications of various soil and water conservation technologies for crop production in Ethiopia's Nile River Basin. The analysis identifies technologies that increase and decrease crop production risk-with risk defined as the degree of yield variability-for the purpose of isolating which technologies are best suited to particular regions and agroecological zones. These results could be used to improve the geographical targeting of soil conservation techniques as part of efforts to promote farm-level adaptation to climate change.
openalex: W3125140969 mag: 3125140969
Keywords: openalex:import

Soil and water conservation technologies: A buffer against production risk in the face of climate change?: Insights from the Nile Basin in Ethiopia - Kato, Edward; Ringler, Claudia; Yesuf, Mahmud; Bryan, Elizabeth (RePEc: Research Papers in Economics, 2009)
This study investigates the impact of different soil and water conservation technologies on the variance of crop production in Ethiopia to determine the risk implications of the different technologies in different regions and rainfall zones. Given the production risks posed by climate change, such information can be used by decision makers to identify appropriate agricultural practices that act as a buffer against climate change. Using a household- and plot-level data set, we apply the Just and Pope framework using a Cobb-Douglas production function to investigate the impact of various soil and water conservation technologies on average crop yields and the variance of crop yields, while controlling for several household- and plot-level Results show that soil and water conservation investments perform differently in different rainfall areas and regions of Ethiopia, which underscores the importance of careful geographical targeting when promoting and scaling up soil and water conservation technologies. We find that although soil bunds, stone bunds, grass strips, waterways, and contours all have very significant positive impacts on average crop yields in low-rainfall areas, only soil bunds have significant risk-reducing effects in these areas with low agricultural potential. We also find that irrigation and use of improved seeds have insignificant risk-reducing effects in low-rainfall areas, suggesting that—as currently implemented—these interventions may not be appropriate adaptation strategies for these environments. Regionally, in the low-rainfall areas we find significant spatial heterogeneity, with soil bunds being risk reducing in Oromiya and Amhara, and stone bunds, grass strips, and waterways being risk reducing in the Southern Nations, Nationalities, and Peoples Region. Irrigation was only risk reducing in the high-rainfall areas of Benishangul-Gumuz. These results remain robust even after controlling for the major crops grown on the plot. Results show that soil and water conservation technologies have significant impacts on reducing production risk in Ethiopia and could be part of the country's climate-proofing strategy. However, results also show that one-size-fits-all recommendations are not appropriate given the differences in agro-ecology and other confounding factors. from authors' abstract
openalex: W3125514026 mag: 3125514026
Keywords: openalex:import

Adaptation to climate change in Ethiopia and South Africa: options and constraints - Bryan, Elizabeth; Deressa, Temesgen; Gbetibouo, Glwadys Aymone; Ringler, Claudia (Environmental Science & Policy, 2009)
Climate change is expected to adversely affect agricultural production in Africa. Because agricultural production remains the main source of income for most rural communities in the region, adaptation of the agricultural sector is imperative to protect the livelihoods of the poor and to ensure food security. A better understanding of farmers’ perceptions of climate change, ongoing adaptation measures, and the decision-making process is important to inform policies aimed at promoting successful adaptation strategies for the agricultural sector. Using data from a survey of 1800 farm households in South Africa and Ethiopia, this study presents the adaptation strategies used by farmers in both countries and analyzes the factors influencing the decision to adapt. We find that the most common adaptation strategies include: use of different crops or crop varieties, planting trees, soil conservation, changing planting dates, and irrigation. However, despite having perceived changes in temperature and rainfall, a large percentage of farmers did not make any adjustments to their farming practices. The main barriers to adaptation cited by farmers were lack of access to credit in South Africa and lack of access to land, information, and credit in Ethiopia. A probit model is used to examine the factors influencing farmers’ decision to adapt to perceived climate changes. Factors influencing farmers’ decision to adapt include wealth, and access to extension, credit, and climate information in Ethiopia; and wealth, government farm support, and access to fertile land and credit in South Africa. Using a pooled dataset, an analysis of the factors affecting the decision to adapt to perceived climate change across both countries reveals that farmers were more likely to adapt if they had access to extension, credit, and land. Food aid, extension services, and information on climate change were found to facilitate adaptation among the poorest farmers. We conclude that policy-makers must create an enabling environment to support adaptation by increasing access to information, credit and markets, and make a particular effort to reach small-scale subsistence farmers, with limited resources to confront climate change.
openalex: W2011578237 mag: 2011578237
Keywords: openalex:import

Adaptation to climate change in Ethiopia and South Africa: options and constraints - Bryan, Elizabeth; Deressa, Temesgen; Gbetibouo, Glwadys Aymone; Ringler, Claudia (Environmental Science & Policy, 2009)
Climate change is expected to adversely affect agricultural production in Africa. Because agricultural production remains the main source of income for most rural communities in the region, adaptation of the agricultural sector is imperative to protect the livelihoods of the poor and to ensure food security. A better understanding of farmers’ perceptions of climate change, ongoing adaptation measures, and the decision-making process is important to inform policies aimed at promoting successful adaptation strategies for the agricultural sector. Using data from a survey of 1800 farm households in South Africa and Ethiopia, this study presents the adaptation strategies used by farmers in both countries and analyzes the factors influencing the decision to adapt. We find that the most common adaptation strategies include: use of different crops or crop varieties, planting trees, soil conservation, changing planting dates, and irrigation. However, despite having perceived changes in temperature and rainfall, a large percentage of farmers did not make any adjustments to their farming practices. The main barriers to adaptation cited by farmers were lack of access to credit in South Africa and lack of access to land, information, and credit in Ethiopia. A probit model is used to examine the factors influencing farmers’ decision to adapt to perceived climate changes. Factors influencing farmers’ decision to adapt include wealth, and access to extension, credit, and climate information in Ethiopia; and wealth, government farm support, and access to fertile land and credit in South Africa. Using a pooled dataset, an analysis of the factors affecting the decision to adapt to perceived climate change across both countries reveals that farmers were more likely to adapt if they had access to extension, credit, and land. Food aid, extension services, and information on climate change were found to facilitate adaptation among the poorest farmers. We conclude that policy-makers must create an enabling environment to support adaptation by increasing access to information, credit and markets, and make a particular effort to reach small-scale subsistence farmers, with limited resources to confront climate change.
openalex: W2011578237 mag: 2011578237
Keywords: openalex:import; openalex:yes

Adaptation to climate change in Ethiopia and South Africa: options and constraints - Bryan, Elizabeth; Deressa, Temesgen; Gbetibouo, Glwadys Aymone; Ringler, Claudia (Environmental Science & Policy, 2009)
Climate change is expected to adversely affect agricultural production in Africa. Because agricultural production remains the main source of income for most rural communities in the region, adaptation of the agricultural sector is imperative to protect the livelihoods of the poor and to ensure food security. A better understanding of farmers’ perceptions of climate change, ongoing adaptation measures, and the decision-making process is important to inform policies aimed at promoting successful adaptation strategies for the agricultural sector. Using data from a survey of 1800 farm households in South Africa and Ethiopia, this study presents the adaptation strategies used by farmers in both countries and analyzes the factors influencing the decision to adapt. We find that the most common adaptation strategies include: use of different crops or crop varieties, planting trees, soil conservation, changing planting dates, and irrigation. However, despite having perceived changes in temperature and rainfall, a large percentage of farmers did not make any adjustments to their farming practices. The main barriers to adaptation cited by farmers were lack of access to credit in South Africa and lack of access to land, information, and credit in Ethiopia. A probit model is used to examine the factors influencing farmers’ decision to adapt to perceived climate changes. Factors influencing farmers’ decision to adapt include wealth, and access to extension, credit, and climate information in Ethiopia; and wealth, government farm support, and access to fertile land and credit in South Africa. Using a pooled dataset, an analysis of the factors affecting the decision to adapt to perceived climate change across both countries reveals that farmers were more likely to adapt if they had access to extension, credit, and land. Food aid, extension services, and information on climate change were found to facilitate adaptation among the poorest farmers. We conclude that policy-makers must create an enabling environment to support adaptation by increasing access to information, credit and markets, and make a particular effort to reach small-scale subsistence farmers, with limited resources to confront climate change.
openalex: W2011578237 mag: 2011578237
Keywords: openalex:import

How can African agriculture adapt to climate change: Economywide impacts of climate change on agriculture in Sub-Saharan Africa - Calzadilla, Alvaro; Zhu, Tingju; Rehdanz, Katrin; Tol, Richard; Ringler, Claudia (RePEc: Research Papers in Economics, 2009)
Approximately 80 percent of poor people in Sub-Saharan Africa continue to depend on the agricultural sector for their livelihoods, but-unlike in other regions of the world-agriculture in Sub-Saharan Africa is characterized by very low yields due to agroecological features, poor access to services, lack of knowledge and inputs, and low levels of investment in infrastructure and irrigation. In addition, high population growth rates, especially in rural areas, intensify pressure on agricultural production and natural resources and further complicate the challenge of reducing poverty. Against this background, potential climate change poses a significant additional challenge to the future of agriculture in the region. Climate change could cause serious deterioration of rural livelihoods and increase food insecurity in Sub-Saharan Africa. Given these multiple challenges, the region's smallholders and pastoralists must adapt, in particular by adopting technologies to increase productivity and the stability and resilience of their production systems.
openalex: W1560958226 mag: 1560958226
Keywords: openalex:import

Analyzing the Determinants of Farmers’ Choice of Adaptation Methods and Perceptions of Climate Change in the Nile Basin of Ethiopia - Deressa, Temesgen; Hassan, Hamdy; Alemu, Tekie; Yesuf, Mahmud; Ringler, Claudia (Research briefs, 2008)
This study identifies the major methods used by farmers to adapt to climate change in the Nile Basin of Ethiopia, the factors that affect their choice of method, and the barriers to adaptation. The methods identified include use of different crop varieties, tree planting, soil conservation, early and late planting, and irrigation. Results from the discrete choice model employed indicate that the level of education, gender, age, and wealth of the head of household; access to extension and credit; information on climate, social capital, agroecological settings, and temperature all influence farmers' choices. The main barriers include lack of information on adaptation methods and financial constraints. Moreover, the analysis reveals that age of the household head, wealth, information on climate change, social capital, and agroecological settings have significant effects on farmers' perceptions of climate change. from authors' abstract
openalex: W3122805052 mag: 3122805052
Keywords: openalex:import

Determinants of farmers’ choice of adaptation methods to climate change in the Nile Basin of Ethiopia - Deressa, Temesgen; Hassan, Rashid M.; Ringler, Claudia; Alemu, Tekie; Yesuf, Mahmud (Global Environmental Change, 2009)
This study identifies the major methods used by farmers to adapt to climate change in the Nile Basin of Ethiopia, the factors that affect their choice of method, and the barriers to adaptation. The methods identified include use of different crop varieties, tree planting, soil conservation, early and late planting, and irrigation. Results from the discrete choice model employed indicate that the level of education, gender, age, and wealth of the head of household; access to extension and credit; information on climate, social capital, agroecological settings, and temperature all influence farmers’ choices. The main barriers include lack of information on adaptation methods and financial constraints.
openalex: W1977827751 mag: 1977827751
Keywords: openalex:import

Analyzing the determinants of farmers' choice of adaptation methods and perceptions of climate change in the Nile Basin of Ethiopia: - Deressa, Temesgen; Hassan, Rashid M.; Alemu, Tekie; Yesuf, Mahmud; Ringler, Claudia (RePEc: Research Papers in Economics, 2008)
This study identifies the major methods used by farmers to adapt to climate change in the Nile Basin of Ethiopia, the factors that affect their choice of method, and the barriers to adaptation. The methods identified include use of different crop varieties, tree planting, soil conservation, early and late planting, and irrigation. Results from the discrete choice model employed indicate that the level of education, gender, age, and wealth of the head of household; access to extension and credit; information on climate, social capital, agroecological settings, and temperature all influence farmers' choices. The main barriers include lack of information on adaptation methods and financial constraints. Moreover, the analysis reveals that age of the household head, wealth, information on climate change, social capital, and agroecological settings have significant effects on farmers' perceptions of climate change. from authors' abstract
openalex: W1513173206 mag: 1513173206
Keywords: openalex:import

Determinants of farmers’ choice of adaptation methods to climate change in the Nile Basin of Ethiopia - Deressa, Temesgen; Hassan, Rashid M.; Ringler, Claudia; Alemu, Tekie; Yesuf, Mahmud (Global Environmental Change, 2009)
This study identifies the major methods used by farmers to adapt to climate change in the Nile Basin of Ethiopia, the factors that affect their choice of method, and the barriers to adaptation. The methods identified include use of different crop varieties, tree planting, soil conservation, early and late planting, and irrigation. Results from the discrete choice model employed indicate that the level of education, gender, age, and wealth of the head of household; access to extension and credit; information on climate, social capital, agroecological settings, and temperature all influence farmers’ choices. The main barriers include lack of information on adaptation methods and financial constraints.
openalex: W1977827751 mag: 1977827751
Keywords: openalex:import

Determinants of farmers’ choice of adaptation methods to climate change in the Nile Basin of Ethiopia - Deressa, Temesgen; Hassan, Rashid M.; Ringler, Claudia; Alemu, Tekie; Yesuf, Mahmud (Global Environmental Change, 2009)
This study identifies the major methods used by farmers to adapt to climate change in the Nile Basin of Ethiopia, the factors that affect their choice of method, and the barriers to adaptation. The methods identified include use of different crop varieties, tree planting, soil conservation, early and late planting, and irrigation. Results from the discrete choice model employed indicate that the level of education, gender, age, and wealth of the head of household; access to extension and credit; information on climate, social capital, agroecological settings, and temperature all influence farmers’ choices. The main barriers include lack of information on adaptation methods and financial constraints.
openalex: W1977827751 mag: 1977827751
Keywords: openalex:import

Determinants of farmers’ choice of adaptation methods to climate change in the Nile Basin of Ethiopia - Deressa, Temesgen; Hassan, Rashid M.; Ringler, Claudia; Alemu, Tekie; Yesuf, Mahmud (Global Environmental Change, 2009)
This study identifies the major methods used by farmers to adapt to climate change in the Nile Basin of Ethiopia, the factors that affect their choice of method, and the barriers to adaptation. The methods identified include use of different crop varieties, tree planting, soil conservation, early and late planting, and irrigation. Results from the discrete choice model employed indicate that the level of education, gender, age, and wealth of the head of household; access to extension and credit; information on climate, social capital, agroecological settings, and temperature all influence farmers’ choices. The main barriers include lack of information on adaptation methods and financial constraints.
openalex: W1977827751 mag: 1977827751
Keywords: openalex:import; openalex:yes

Analyzing the determinants of farmers' choice of adaptation methods and perceptions of climate change in the Nile Basin of Ethiopia: - Deressa, Temesgen; Hassan, Rashid M.; Alemu, Tekie; Yesuf, Mahmud; Ringler, Claudia (RePEc: Research Papers in Economics, 2008)
This study identifies the major methods used by farmers to adapt to climate change in the Nile Basin of Ethiopia, the factors that affect their choice of method, and the barriers to adaptation. The methods identified include use of different crop varieties, tree planting, soil conservation, early and late planting, and irrigation. Results from the discrete choice model employed indicate that the level of education, gender, age, and wealth of the head of household; access to extension and credit; information on climate, social capital, agroecological settings, and temperature all influence farmers' choices. The main barriers include lack of information on adaptation methods and financial constraints. Moreover, the analysis reveals that age of the household head, wealth, information on climate change, social capital, and agroecological settings have significant effects on farmers' perceptions of climate change. from authors' abstract
openalex: W1513173206 mag: 1513173206
Keywords: openalex:import

Determinants of farmers’ choice of adaptation methods to climate change in the Nile Basin of Ethiopia - Deressa, Temesgen; Hassan, Rashid M.; Ringler, Claudia; Alemu, Tekie; Yesuf, Mahmud (Global Environmental Change, 2009)
This study identifies the major methods used by farmers to adapt to climate change in the Nile Basin of Ethiopia, the factors that affect their choice of method, and the barriers to adaptation. The methods identified include use of different crop varieties, tree planting, soil conservation, early and late planting, and irrigation. Results from the discrete choice model employed indicate that the level of education, gender, age, and wealth of the head of household; access to extension and credit; information on climate, social capital, agroecological settings, and temperature all influence farmers’ choices. The main barriers include lack of information on adaptation methods and financial constraints.
openalex: W1977827751 mag: 1977827751
Keywords: openalex:import; openalex:yes

Analyzing the determinants of farmers' choice of adaptation methods and perceptions of climate change in the Nile Basin of Ethiopia: - Deressa, Temesgen; Hassan, Rashid M.; Alemu, Tekie; Yesuf, Mahmud; Ringler, Claudia (RePEc: Research Papers in Economics, 2008)
This study identifies the major methods used by farmers to adapt to climate change in the Nile Basin of Ethiopia, the factors that affect their choice of method, and the barriers to adaptation. The methods identified include use of different crop varieties, tree planting, soil conservation, early and late planting, and irrigation. Results from the discrete choice model employed indicate that the level of education, gender, age, and wealth of the head of household; access to extension and credit; information on climate, social capital, agroecological settings, and temperature all influence farmers' choices. The main barriers include lack of information on adaptation methods and financial constraints. Moreover, the analysis reveals that age of the household head, wealth, information on climate change, social capital, and agroecological settings have significant effects on farmers' perceptions of climate change. from authors' abstract
openalex: W1513173206 mag: 1513173206
Keywords: openalex:import

Determinants of farmers’ choice of adaptation methods to climate change in the Nile Basin of Ethiopia - Deressa, Temesgen; Hassan, Rashid M.; Ringler, Claudia; Alemu, Tekie; Yesuf, Mahmud (Global Environmental Change, 2009)
This study identifies the major methods used by farmers to adapt to climate change in the Nile Basin of Ethiopia, the factors that affect their choice of method, and the barriers to adaptation. The methods identified include use of different crop varieties, tree planting, soil conservation, early and late planting, and irrigation. Results from the discrete choice model employed indicate that the level of education, gender, age, and wealth of the head of household; access to extension and credit; information on climate, social capital, agroecological settings, and temperature all influence farmers’ choices. The main barriers include lack of information on adaptation methods and financial constraints.
openalex: W1977827751 mag: 1977827751
Keywords: openalex:import

Analyzing the determinants of farmers' choice of adaptation methods and perceptions of climate change in the Nile Basin of Ethiopia: - Deressa, Temesgen; Hassan, Rashid M.; Alemu, Tekie; Yesuf, Mahmud; Ringler, Claudia (RePEc: Research Papers in Economics, 2008)
This study identifies the major methods used by farmers to adapt to climate change in the Nile Basin of Ethiopia, the factors that affect their choice of method, and the barriers to adaptation. The methods identified include use of different crop varieties, tree planting, soil conservation, early and late planting, and irrigation. Results from the discrete choice model employed indicate that the level of education, gender, age, and wealth of the head of household; access to extension and credit; information on climate, social capital, agroecological settings, and temperature all influence farmers' choices. The main barriers include lack of information on adaptation methods and financial constraints. Moreover, the analysis reveals that age of the household head, wealth, information on climate change, social capital, and agroecological settings have significant effects on farmers' perceptions of climate change. from authors' abstract
openalex: W1513173206 mag: 1513173206
Keywords: openalex:import

The impact of climate change and adaptation on food production in low income countries: Evidence from the Nile basin, Ethiopia - Yesuf, Mahmud; Falco, Salvatore Di; Deressa, Temesgen; Ringler, Claudia; Köhlin, Gunnar (RePEc: Research Papers in Economics, 2008)
Growing consensus in the scientific community indicates that higher temperatures and changing precipitation levels resulting from climate change will depress crop yields in many countries over the coming decades. This is particularly true in low-income countries, where adaptive capacity is low. Many African countries are particularly vulnerable to climate change because their economies largely depend on climate-sensitive agricultural production. This brief is based on a study that used household survey data to analyze the impact of climate change on food production in the Nile Basin of Ethiopia. The study also examined the factors influencing adaptation and the implications of various adaptation strategies for farm productivity. from text
openalex: W1482244041 mag: 1482244041
Keywords: openalex:import

How can African agriculture adapt to climate change: Analysis of the determinants of farmers' choice of adaptation methods and perceptions of climate change in the Nile Basin of Ethiopia: - Deressa, Temesgen; Hassan, Rashid M.; Ringler, Claudia; Alemu, Tekie; Yesuf, Mahmud (Research briefs, 2008)
Ethiopia's agricultural sector, which is dominated by smallscale, mixed-crop, and livestock farming, is the mainstay of the country's economy. It constitutes more than half of the country's gross domestic product, generates more than 85 percent of foreign exchange earnings, and employs about 80 percent of the population. Unfortunately, Ethiopia's dependence on agriculture makes the country particularly vulnerable to the adverse impacts of climate change on crop and livestock production. Thus, a deeper understanding of the complex interdependence between changing climatic conditions and Ethiopia's agricultural sector- together with adaptation options-is crucial. Additional information about farmers' awareness of climate change and current adaptation approaches would assist policymakers in their efforts to decrease the country's vulnerability to the adverse impacts of climate change. This brief is based on a study that endeavors to guide policymakers on ways to promote greater adaptation by identifying the household characteristics that increase farmers' awareness of climate change and influence farmers' decision to adapt.
openalex: W2607154436 mag: 2607154436
Keywords: openalex:import

Economywide impacts of climate change on agriculture in Sub-Saharan Africa: - Calzadilla, Alvaro; Zhu, Tingju; Rehdanz, Katrin; Tol, Richard S.J.; Ringler, Claudia (RePEc: Research Papers in Economics, 2009)
Two possible adaptation options to climate change for Sub-Saharan Africa are analyzed under the SRES B2 scenario. The first scenario doubles the irrigated area in Sub-Saharan Africa by 2050, compared to the baseline, but keeps total crop area constant. The second scenario increases both rainfed and irrigated crop yields by 25 percent for all Sub-Saharan African countries. The two adaptation scenarios are analyzed with IMPACT, a partial equilibrium agricultural sector model combined with a water simulation module, and with GTAP-W, a general equilibrium model including water resources. The methodology combines the advantages of a partial equilibrium approach, which considers detailed water-agriculture linkages, with a general equilibrium approach, which takes into account linkages between agriculture and nonagricultural sectors and includes a full treatment of factor The efficacy of the two scenarios as adaptation measures to cope with climate change is discussed. Due to the limited initial irrigated area in the region, an increase in agricultural productivity achieves better outcomes than an expansion of irrigated area. Even though Sub-Saharan Africa is not a key contributor to global food production or irrigated food production, both scenarios help lower world food prices, stimulating national and international food markets. from authors' abstract
openalex: W3124999701 mag: 3124999701
Keywords: openalex:import

How can African agriculture adapt to climate change: The impact of climate change and adaptation on food production in low-income countries: Evidence from the Nile Basin, Ethiopia [in Amharic] - Yesuf, Mahmud; Falco, Salvatore Di; Deressa, Temesgen; Ringler, Claudia; Köhlin, Gunnar (Research briefs, 2008)
Growing consensus in the scientific community indicates that higher temperatures and changing precipitation levels resulting from climate change will depress crop yields in many countries over the coming decades. This is particularly true in low-income countries, where adaptive capacity is low. Many African countries are particularly vulnerable to climate change because their economies largely depend on climate-sensitive agricultural production. This brief is based on a study that used household survey data to analyze the impact of climate change on food production in the Nile Basin of Ethiopia. The study also examined the factors influencing adaptation and the implications of various adaptation strategies for farm productivity. from text
openalex: W2610028307 mag: 2610028307
Keywords: openalex:import

How can African agriculture adapt to climate change: Economywide impacts of climate change on agriculture in Sub-Saharan Africa: - Calzadilla, Alvaro; Zhu, Tingju; Rehdanz, Katrin; Tol, Richard S.J.; Ringler, Claudia (Research briefs, 2009)
Approximately 80 percent of poor people in Sub-Saharan Africa continue to depend on the agricultural sector for their livelihoods, but-unlike in other regions of the world-agriculture in Sub-Saharan Africa is characterized by very low yields due to agroecological features, poor access to services, lack of knowledge and inputs, and low levels of investment in infrastructure and irrigation. In addition, high population growth rates, especially in rural areas, intensify pressure on agricultural production and natural resources and further complicate the challenge of reducing poverty. Against this background, potential climate change poses a significant additional challenge to the future of agriculture in the region. Climate change could cause serious deterioration of rural livelihoods and increase food insecurity in Sub-Saharan Africa. Given these multiple challenges, the region's smallholders and pastoralists must adapt, in particular by adopting technologies to increase productivity and the stability and resilience of their production systems.
openalex: W3123774066 mag: 3123774066
Keywords: openalex:import

The impact of climate change and adaptation on food production in low-income countries: Evidence from the Nile Basin, Ethiopia [in Amharic] - Yesuf, Mahmud; Falco, Salvatore Di; Deressa, Temesgen; Ringler, Claudia; Köhlin, Gunnar (Research briefs, 2008)
Growing consensus in the scientific community indicates that higher temperatures and changing precipitation levels resulting from climate change will depress crop yields in many countries over the coming decades. This is particularly true in low-income countries, where adaptive capacity is low. Many African countries are particularly vulnerable to climate change because their economies largely depend on climate-sensitive agricultural production. This brief is based on a study that used household survey data to analyze the impact of climate change on food production in the Nile Basin of Ethiopia. The study also examined the factors influencing adaptation and the implications of various adaptation strategies for farm productivity. from text
openalex: W3124511858 mag: 3124511858
Keywords: openalex:import